Manajemen kelas bagi Guru SMA Insan Cendekia Syech Yusuf Kabupaten Gowa - Arismunandar Arismunandar; Nurhikmah H (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Community Partnership Program (PKM) activity was carried out at Insan Cendekia Syech Yusuf Gowa High School.Partner problems faced by teachers are 1. Teachers have limitations in creating a comfortable learning atmosphere. 2. Teachershave limitations in efficient classroom management. The purpose of this PKM activity is to train Gowa Insan Scholar HighSchool teachers to be able to obtain material about efficient and good classroom management and be able to apply it to classroomlearning so that the expected learning objectives can be achieved. Participants who took part in this activity consisted of 31participants with two speakers and three assistants. The results obtained from this training activity indicate that the teacher gainedknowledge about managing the classroom efficiently through the practice that was carried out.